Downsizing - Roberts, Ralph R., 1958-; Roberts, Kathleen; Kraynak, Joe; Roberts, Kyle (--For dummies., 2023)
Organize, declutter, donate---downsize and simplify your life. Downsizing For Dummies provides you with strategies to downsize your life by moving to a smaller home, decluttering, simplifying your budget, and saving more money. You'll find tips to help decrease your cost of living, lower your home maintenance costs, protect and leverage your assets, and decide whether downsizing is right for you and your family. After downsizing your life, you'll save time on household chores and gain the freedom and flexibility that come with having fewer possessions. What will you do with all the time you save? Downsizing For Dummies will help you understand the benefits of living simply!...This book is for anyone who is ready to live clutter-free and to downsize. It's the perfect Dummies guide for homeowners looking to save money, plus real estate brokers who are working with clients who are downsizing, and designers and builders of new homes who want to stay on top of the downsizing trend.